A qualitative analysis of Australian women’s understanding and experiences related to the introduction of solids Nutrition and Nurture in Infancy and Childhood - Scott, Jane; Begley, Andrea; Giglia, Roslyn; Paganin, A. (Wiley, 2015)
The current Australian Infant Feeding Guidelines (AIFG) recommend that infants receive solids at around 6 months of age (National Health and Medical Research Council 2012), by 5 months of age however 70% of Australian infants have started solids. While there is some evidence that Western Australian mothers are introducing solids later than they did in 2003 when the recommendation was to introduce solids between 4-6 months, relatively little is known about mother’s understanding of the AIFG and reasons why the majority choose not, or are unable, to adhere to the AIFG. The objectives of this research were to 1) identify women’s familiarity with infant feeding recommendations; 2) describe their actual infant feeding experiences; and 3) explore socio-ecological factors that determine women’s decisions and practices related to the introduction of solids. Seven focus group interviews were conducted consisting of mothers (n=42) of infants under 18 months recruited predominantly from areas of medium socioeconomic disadvantage in Perth, Western Australia. Interviews were audio-taped, transcribed and thematically interpreted. The mean age of the infants of the focus group participants was 9.6 months and mean age of introduction of solids was 4.3 months (range 1.2 to 7.5 months). Just under half of participant mothers indicated they had heard of the AIFG but only half of them correctly identified 6 months as the recommended age for introducing solids. Several themes emerged from the analysis related to the social construction of infants, infant autonomy and trust in sources of information on feeding infants that provide insights into the reasons for the early introduction of solids and lack of guideline awareness. In particular, mothers who introduced solids very early (before 4 months) generally were seeking a solution to a real or perceived problem such as colic or infant sleeplessness. Significant others who influenced the decision to introduce solids included maternal grandmothers, other family members, health professionals and to a lesser extent the infant’s father. Women often felt pressure from family members who on occasion were the first to introduce, (usually without permission) to the infant. Social media such as Facebook was identified by several women as both a source of advice and a subtle form of peer-pressure with starting solids being seen as a developmental milestone with bragging rights. In keeping with other research women cited advice which confirmed their own decisions (Hoddinott et al. 2012) with very few expressing regret in introducing solids when they did. Relatively few women were aware of the scientific evidence underpinning the AIFG which were seen generally as an alternative form of advice as opposed to a set of health recommendations to be adhered to at all costs.